The performance of Sadem Theater in memory of al-Zahiyah in mass worship campaigns in Iraq 1988 - Hussein, Prof. Dr. Muntaha Tariq Hussein (Sulaimani Journal for Humanities, 2024)
The theater has varied in its philosophical, artistic, and social approaches, necessitating the development of approaches and methodologies that satisfy the needs of the theater audience, reflecting their innermost feelings and the issues their society addresses. These issues permeate the social fabric and are presented within a dramatic and aesthetic framework that resonates with their emotions, anxieties, and inner turmoil. This has led to the need for a philosophical and thought-provoking theatrical framework, one that challenges and experiments to deliver a message emanating from the stage. This message is conveyed within an aesthetic space that the audience experiences through a compelling and evocative medium, employing the memory of the victim and the trauma they have endured, whether through physical violence, rape, war, murder, or other inhumane means. Shock Theatre has gained significant cultural and aesthetic importance, its mission being to reveal the events of genocidal campaigns and to uncover the memories of victims within those campaigns. It aims to shock the audience, causing a kind of mental disturbance through its boldness and rigor, illuminating a theatrical experience that resonates deeply with the viewer, allowing them to feel the profound emotions presented on stage. This creates a space for catharsis and awareness stemming from the fear, pity, and human cruelty that surround modern humanity. While it approaches Aristotle's concept of catharsis, it also expands upon it, ultimately leading to a process of awareness of what is happening, as noted by the English writer Sarah Keane, a pioneer of Shock Theatre. This study attempts to develop a theatrical framework for the memory of victims of the genocide perpetrated against the Kurdish national and cultural identity in Iraq during the Ba'athist regime in the 1980s. Based on the Shock Theatre experience, it aims to stir the audience's inner feelings, conveying an awareness of memory and the truths it holds, within an aesthetically compelling framework created by both the sender and receiver.
Keywords: Theater; shock; genocide; ethnic cleansing; building a different consciousness